A multifaceted intervention to prevent American cutaneous leishmaniasis in Colombia: results of a group-randomized trial (2006)
ABSTRACT: Introduction. American cutaneous leishmaniasis is endemic in Colombia, where approximately 6.000 new cases are reported every year. Current prevention and control measures are restrictedto the diagnosis and treatment of cases. Objective. To evaluate the efficacy of a multifaceted intervention to prevent the transmission ofLeishmania in the endemic focus of Tumaco, on the Pacific Coast of Colombia. Materials and methods. A group-randomized trial was conducted. Twenty villages were matchedaccording to prevalence of Leishmania infection, number of inhabitants and level of communityparticipation, and then randomly assigned to intervention or control. The intervention includeddeltamethrin-impregnated bednets, repellent (20% diethyltoluamide and 0.5% permethrin), modification of sand fly resting sites, and health education. Villages were under surveillance forone year and the use of the intervention measures monitored. The incidence of Americancutaneous leishmaniasis and Leishmania infection in the two groups were compared, adherenceto the intervention and adverse events were monitored, and the results were adjusted forvillage intraclass correlation. Results. Ten cases of American cutaneous leishmaniasis were confirmed in the interventionand 23 in the control group, OR = 0.42, 95% CI 0.14-1.26. The intervention had a greater effectin children < 10 years old, in people living on the periphery of the village and in villages with aprevalence of infection in small children > 1%. Adverse events associated with the use of thebednets and the repellent were reported in 2% of the participants and were always mild. Conclusion. Incident cases of American cutaneous leishmaniasis were reduced by 58% in theintervention group. However, the small number of cases renders the effect estimate impreciseand precludes us to claim a protective effect for the intervention. Specific populations could bethe targets of simpler and more cost-effective interventions in the future.